Does the Concept of “Sensitization” Provide a Plausible Mechanism for the Putative Link Between the Environment and Schizophrenia? - Collip, Dina (Oxford University Press, 2008)
Previous evidence reviewed in Schizophrenia Bulletin suggests the importance of a range of different environmental factors in the development of psychotic illness. It is unlikely, however, that the diversity of environmental influences associated with schizophrenia can be linked to as many different underlying mechanisms. There is evidence that environmental exposures may induce, in interaction with (epi)genetic factors, psychological or physiological alterations that can be traced to a final common pathway of cognitive biases and/or altered dopamine neurotransmission, broadly referred to as “sensitization,” facilitating the onset and persistence of psychotic symptoms. At the population level, the behavioral phenotype for sensitization may be examined by quantifying, in populations exposed to environmental risk factors associated with stress or dopamine-agonist drugs, (1) the increased rate of persistence (indicating lasting sensitization) of normally transient developmental expressions of subclinical psychotic experiences and (2) the subsequent increased rate of transition to clinical psychotic disorder.